Pathshala: Student Information Management using Cutting-Edge Technology - Saud, Pradip Singh; Chand, Apil; Chaurasia, Nitesh Kumar; Bastola, Laxmi Prasad (Journal of Soft Computing Paradigm, 2023)
An Education Information Management System is developed using the Flutter framework integrated with Firebase for data storage and authentication. The system addresses the challenges faced by educational institutions in managing student information, attendance, grades, and communication with parents. Traditional methods of managing school-related tasks are often cumbersome, time-consuming, and error-prone. Thus, there is a need for an efficient and user-friendly solution that can streamline these processes and enhance productivity. The development of the school management system utilizes the Flutter framework, a cross-platform development tool, to create a mobile application as well as web application. Firebase, a comprehensive cloud-based platform, was integrated to handle data storage, authentication, and communication. The system focused on meeting the needs of school administrators, teachers, students, and parents. Key features included student enrollment, attendance tracking, grade management, and notice announcement functionalities. The implementation of this system resulted in significant benefits, such as easier student registration, efficient attendance tracking, streamlined grade management, improved communication, and enhanced engagement among administrators, teachers, students, and parents.
Keywords: Flutter; Cross-platform; Firebase; authentication